Protamine Promotes Direct Electron Transfer Between Shewanella Oneidensis Cells and Carbon Nanomaterials in Bacterial Biocomposites. Issue 9 (23rd April 2019) - Pinck, Stéphane; Jorand, Frédéric P. A.; Xu, Mengjie; Etienne, Mathieu
Abstract: Invited for this month's cover picture is the group of Dr. Mathieu Etienne from Centre National de la Recherche Scientifique (CNRS, France). The cover picture shows the building block of the bacterial biocomposite made of Shewanella oneidensis, multi‐walled carbon nanotubes, and protamine. The close look at the bacterial membrane shows how protamine, which is positively charged (in blue), promotes self‐assembly between the negatively charged polymers on the bacterial membrane surface (in red) and the negative surface of multi‐walled carbon nanotubes, allowing direct electron transfer reactions. The background of the image is a detail of a scanning electron microscopy image of the biocomposite deposited on a glassy carbon surface, forming the so‐called electroactive artificial biofilm. Read the full text of the Article at10.1002/celc.201801751 . Abstract : "Protamine induces the self‐assembly of Shewanella oneidensis cells with carbon nanomaterials such as multi‐walled carbon nanotubes or Ketjen black. The biocomposites that are produced can be deposited on electrodes to serve as electroactive artificial biofilms. Direct electron transfer reactions are promoted by protamine in these biofilms and maximum current densities on the order of 1 A m −2 are reached for fumarate reduction…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding article on10.1002/celc.201801751